Identification and Mapping of Wastelands in Tonk District, Rajasthan, Using Remote Sensing and their Management Options - Kumar, Suresh; Chaudhary, J S; Gupta, K N (Annals of Arid Zone, 2025)
Seven types of wastelanlds were identified and mapped through visual interpretation of Landsat TM FCCs of semi-arid Tank district in Rajasthan. Wastelanlds in the district cover 21.04Â°0 area, of which the maximum was under degraded grazinglanlds (45.2%). The status of degradation of these wastelands were verified from field: The reclamation options, including soil and water conservation measures, as well as plantation of suitable species. were also worked out.